Descriptive Analysis on Use of Digital Resources: A Study of Socio-Demographic Variations - Pooja Dhakal (Journal of Development Review, 2025)
This paper investigates the influence of key socio-demographic factors: gender, education level, and geographic location on the use of digital resources among users at Nepal Open University. Analysis of symmetric measures reveals no statistically significant relationship between gender and the use of e-resources, with Pearson’s correlation values near zero, indicating a weak and negligible association. Likewise, education level shows a very weak positive but statistically insignificant correlation with e-resources usage and satisfaction. Furthermore, geographic factors based on users’ local administrative divisions (rural municipality, municipality, sub-metropolitan, or metropolitan areas) also exhibit no meaningful correlation with the use of digital resources. These findings suggest that demographic variables such as gender, education level, and geographic location do not significantly influence the experience or perception of digital resources usage. The results highlight the need to explore other underlying factors; potentially behavioral, technological, or institutional that may better explain variations in user satisfaction.